Lived Experience of Solo Parents Nurturing Young Children Seven Years and Below in Virac, Catandaunes - Arcilla, Rose Ann; Zafe, Rica. I; Tuplano, Schultz T.; Canaria, Melchor Z.; Panesa, Rosano R. (Alta Dharma Publisher, 2025)
Background: Solo parenting demands constant balancing of caregiving duties with other responsibilities, highlighting the importance of understanding the unique struggles and coping mechanisms of solo parents, especially in contexts where resources may be limited. Objective: This study explored the lived experiences of solo parents nurturing young children in Virac, Catanduanes, emphasizing the physical, mental, and emotional challenges they encountered. Solo parenting demanded resilience and adaptability, as parents faced financial instability, social stigma, and emotional stress while striving to provide for their children's well-being. Method: The study employed a qualitative phenomenological design, gathering data through in-depth interviews with solo parents to gain insights into their struggles and coping mechanisms. Result: Findings revealed that financial constraints, exhaustion, and limited access to support services significantly impacted their physical and mental health. Many solo parents experienced stress, anxiety, and fatigue due to balancing employment and caregiving without consistent assistance. Despite these challenges, their unwavering commitment to their children served as a source of motivation and strength. Conclusion: The study highlighted the need for accessible government assistance programs, including financial aid, healthcare services, and community-based support networks, to alleviate the burdens of solo parents. Recommendation: It recommended policy enhancements, increased local implementation of solo parent benefits, and the establishment of community-driven interventions to promote the well-being of solo parents and their children in Virac, Catanduanes